Past rewards capture spatial attention and action choices - Camara, E; Manohar, S; Husain, M (2013)
The desire to increase rewards and minimize punishing events is a powerful driver in behaviour. Here, we assess how the value of a location affects subsequent deployment of goal-directed attention as well as involuntary capture of attention on a trial-to-trial basis. By tracking eye position, we investigated whether the ability of an irrelevant, salient visual stimulus to capture gaze (stimulus-driven attention) is modulated by that location's previous value. We found that distractors draw attention to them significantly more if they appear at a location previously associated with a reward, even when gazing towards them now leads to punishments. Within the same experiment, it was possible to demonstrate that a location associated with a reward can also bias subsequent goal-directed attention (indexed by action choices) towards it. Moreover, individuals who were vulnerable to being distracted by previous reward history, as indexed by oculomotor capture, were also more likely to direct their actions to those locations when they had a free choice. Even when the number of initial responses was made to be rewarded and punished stimuli were equalized, the effects of previous reward history on both distractibility and action choices remained. Finally, a covert attention task requiring button-press responses rather than overt gaze shifts demonstrated the same pattern of findings. Thus, past rewards can act to modulate both subsequent stimulus-driven as well as goal-directed attention. These findings reveal that there can be surprising short-term costs of using reward cues to regulate behaviour. They show that current valence information, if maintained inappropriately, can have negative subsequent effects, with attention and action choices being vulnerable to capture and bias, mechanisms that are of potential importance in understanding distractibility and abnormal action choices. © 2013 The Author(s).